PRACTICAL IMPORTANCE OF ANALYSIS OF ACCOUNTS RECEIVABLE IN THE FINANCIAL AND ECONOMIC ACTIVITY OF AN ENTERPRISE (British Journal of Global Ecology and Sustainable Development, 2024)
This article analyzes the significance of the analysis of accounts receivable in the analysis of the financial and economic activities of business entities, its role in improving the financial condition of the enterprise and the state of solvency. The standard level of receivables is discussed as part of the company’s assets. In addition, the receivables turnover ratio and the tasks that should be performed to accelerate it have been studied, as well as an analysis of the turnover period and significant aspects of these obligations. Practical proposals and recommendations for the effective organization of accounting and analysis of accounts receivable in business entities have been developed, and conclusions have been drawn.